Handling Ship Banking MT. Clarice Loaded Church Liquid On PT. Tirtha Dasa Lintas Nusa Belawan - Dimas Puzakesuma; Fadiyah Hani Sabila (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
To find out more closely how the shipping company PT. Tirtha Dasa Lintas Nusa Belawan in handling the docking process of ships loaded with liquid bulk. In this paper, it is explained how to handle berthing of MT ships. CLARICE contains liquid bulk and the ship departure process as well as any agencies involved in the ship berthing process. From handling arrival to departure, the ship must be served efficiently and effectively so that service is maintained well. The methodology used in this paper is first the field observation method and the library approach method. In carrying out ship berthing activities, the agent must notify the ship's arrival to several related agencies such as the harbormaster's office, the PT office. (Persero) Pelindo I, Immigration Office, Customs and Excise Office, Port Authority Office, Port Health Quarantine Office.